DAMPAK PENGGUNAAN QRIS TERHADAP KEPUASAN PENGUNJUNG (Museum Seni Rupa dan Keramik Jakarta) - Annida, Annida; Farida, Farida; Kartika, Dewi gita (Jurnal Ekonomi Dan Bisnis, 2024)
Payment by QR code is a digital payment method that does not require physical contact between the seller and the buyer. Apart from that, the presence of QRIS facilitates various types of payment transactions which can have an impact on visitor satisfaction. The aim of this research is to find out how the implementation of the Indonesian Standard Quick Response Code (QRIS) impacts the level of satisfaction of visitors to art and ceramics museums. This research is field research using descriptive quantitative methods. The research results show that the use of QRIS has a positive and significant effect on customer satisfaction at the Jakarta Fine Arts and Ceramics Museum. While the value given by respondents for visitor satisfaction at the Museum of Fine Arts and Ceramics is very satisfied and the use of QRIS is very useful in carrying out transaction activities, the Museum of Fine Arts and Ceramics still has to improve the quality of service in order to reduce and even eliminate visitor complaints so as to increase the number visit.